2022
DOI: 10.1515/opag-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and knowledge regarding quality and safety of plastic materials used for food packaging

Abstract: The objective of this study is to investigate the consumer perceptions about quality and safety of foods packed in plastic, as well as the impact of plastic materials on human health. To carry out the study, a questionnaire survey about the consumption habits and knowledge about plastic packaging was conducted to a sample of 487 Portuguese adult citizens. The results revealed that most respondents (81%) think about food safety and quality when purchasing foods. Additionally, it was found that the consumer’s kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…With regards to the limitations, it is important to highlight the recruitment of participants, which followed a snowball methodology through internet tools on a convenience sample. As previously mentioned, the easy access, facility of recruitment, and readily verification of will to participate, along with the absence of funding requirement to conduct the survey, all contributed to the option of using a convenience sample, having in mind that studies have referred this as a useful approach to conduct exploratory research [ 13 , 14 , 15 ]. Convenience samples are frequently used in many studies reported on the scientific literature, for surveys about very different topics, precisely due to their advantages [ 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the limitations, it is important to highlight the recruitment of participants, which followed a snowball methodology through internet tools on a convenience sample. As previously mentioned, the easy access, facility of recruitment, and readily verification of will to participate, along with the absence of funding requirement to conduct the survey, all contributed to the option of using a convenience sample, having in mind that studies have referred this as a useful approach to conduct exploratory research [ 13 , 14 , 15 ]. Convenience samples are frequently used in many studies reported on the scientific literature, for surveys about very different topics, precisely due to their advantages [ 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the data collection took place using online tools, while it is known that personal interviews could constitute a more feasible way for the data collection [ 15 ]. Nevertheless, the procedure would be incredibly more expensive, and it would also take more time to collect the data, and eventually it would not be possible to conduct the research without additional funding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation